Family participation to elderly rehabilitation with femoral fracture - Marla Andréia Garcia de Avila; Gilberto José Cação Pereira; Silvia Cristina Mangini Bocchi (Associação Brasileira de Enfermagem, 2015)
ABSTRACTObjective:verify if the mode of care adopted by caregivers favored functional independence recovery by elderly with and without the presence of nervous system disease and mental and behavioral disorders; and, if disease interfered with their functional independence.Method:transversal study, with 12-month follow-up of 89 Brazilian elders (≥ 60 years) after proximal femoral surgery, and their family caregiver.Results:the Functional Independence Measure scores decreased by 0.7 points per year of life, and in the case of presenting nervous system disease and mental and behavioral disorders, this loss amounted to 20.5 points.Conclusion:The incentive to ambulate increased by 18.8 for self-care, 12.8 for self-care, and 11.5 for leisure activities on the Functional Independence Measure. Encouraging movement and ambulation, self-care and leisure activities, especially with those elderly with nervous system diseases and mental and behavioral disorders, is recommended.